2004
DOI: 10.1152/ajpendo.00074.2004
|View full text |Cite
|
Sign up to set email alerts
|

Activity of LKB1 and AMPK-related kinases in skeletal muscle: effects of contraction, phenformin, and AICAR

Abstract: Activation of AMPactivated protein kinase (AMPK) by exercise and metformin is beneficial for the treatment of type 2 diabetes. We recently found that, in cultured cells, the LKB1 tumor suppressor protein kinase activates AMPK in response to the metformin analog phenformin and the AMP mimetic drug 5-aminoimidazole-4-carboxamide-1-␤-D-ribofuranoside (AICAR). We have also reported that LKB1 activates 11 other AMPK-related kinases. The activity of LKB1 or the AMPK-related kinases has not previously been studied in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
245
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 281 publications
(263 citation statements)
references
References 32 publications
15
245
3
Order By: Relevance
“…For example, we 28 and others 7 have shown that an increase in AMPK phosphorylation during myocardial ischemia is accompanied by a stimulation of AMPKK activity. However, we 28 and others 29 found that this activation of AMPKK is not associated with an activation of LKB1. This suggests that either calmodulindependent protein kinase kinase is involved in AMPK phosphorylation during ischemia or that there is a presence of additional, as yet unidentified, AMPKKs in the heart.…”
Section: Ampk Activation During Ischemia/reperfusioncontrasting
confidence: 59%
“…For example, we 28 and others 7 have shown that an increase in AMPK phosphorylation during myocardial ischemia is accompanied by a stimulation of AMPKK activity. However, we 28 and others 29 found that this activation of AMPKK is not associated with an activation of LKB1. This suggests that either calmodulindependent protein kinase kinase is involved in AMPK phosphorylation during ischemia or that there is a presence of additional, as yet unidentified, AMPKKs in the heart.…”
Section: Ampk Activation During Ischemia/reperfusioncontrasting
confidence: 59%
“…The following food groups and food extracts have high AMPKactivating capacity: resveratrol (red grape skin extract) [114][115][116][117][118], nootkatone (grapefruit extract) [119], ajoene (garlic extract) [120], BDIM (cruciferous vegetable extract) [19,121], and many others [122]. Medicines activate AMPK including Asa [16], Met [35], phenformin [123,124], rosiglitazone, and phenobarbital [125,126], and there may be others.…”
Section: Discussionmentioning
confidence: 99%
“…In order to investigate its physiological effects, AMPK is often experimentally activated by either of two agents, phenformin or AICAR. These two drugs activate AMPK by different mechanisms, with AICAR structurally mimicking the endogenous activator AMP, while several different mechanisms involving activation of an AMPK-phosphorylating kinase have been proposed for the effect of phenformin and its analog metformin [43][44][45][46][47][48]. In non-proliferating differentiated hippocampal neurons and in proliferating neuroblastoma SH-SY5Y cells, the present study found that both phenformin and AICAR not only activated AMPK, but also greatly reduced the phosphorylation of Akt on its regulatory Ser/Thr sites.…”
Section: Discussionmentioning
confidence: 99%